Validation and forensic application of a new 19 X-STR loci multiplex system. (November 2021) - Xiao, Cheng; Yang, Xingyi; Liu, Hong; Liu, Changhui; Yu, Zhonghao; Chen, Ling; Liu, Chao
Highlights: A novel 19 X-STR multiplex system was validated for forensic application. This system has high sensitivity and stability, and could yield accurate genotyping results. Population data of Guangdong Han were compared with those from AGCU-X19 STR kit. Abstract: The Microreader™ 19X Direct ID System was a newly developed multiplex PCR kit, which could detect 19 X-chromosomal STR loci (DXS6795, DXS9907, DXS6803, GATA172D05, DXS6807, GATA31E08, DXS7423, DXS6810, DXS101, DXS9902, DXS7133, DXS6800, DXS981, DXS10162, DXS6809, DXS10135, HPRTB, GATA165B12, DXS10079) and the sex determination locus of AMEL simultaneously. Different from other X-STR multiplex PCR kits, no linkage groups are included in this system, so the likelihood ratios could be calculated without the consideration of linkage groups. In this study, PCR conditions, sensitivity, species specificity, stability, DNA mixtures, concordance, stutter, sizing precision and population studies were conducted according to the SWGDAM developmental validation guidelines. The results indicated that this new X-STRs multiplex system was an efficient and reliable detection system, which could facilitate human kinship analysis and identification testing, as a powerful supplementary to autosomal STR kits.